Creating a Child-Friendly District: Strengthening Psychological First Aid Skills for Women’s Empowerment and Child Protection (PPPA) Cadre in Pemalang Regency - Rofi Wahanisa; Pradipta Christy Pratiwi; Rahmawati Prihastuty; Dyah Ayu Rahmawati; Septhian Eka Adiyatma; Satrio Sakti Nugroho (Indonesian Journal of Legal Community Engagement, 2025)
Pemalang Regency continues to record a significant number of cases of violence against women and children, with 62 cases reported by the end of 2024. The main challenges include the limited skills of Women’s Empowerment and Child Protection (PPPA) cadres in handling cases of violence, the lack of ongoing training, and the need for effective violence prevention strategies. To support the initiative of making Pemalang a Child-Friendly District (KLA), it is essential to strengthen the capacity of PPPA cadres so they can respond more effectively to victims of violence. This community service program offers a solution through Psychological First Aid (PFA) psychoeducation for PPPA cadres, which covers: (1) strengthening basic understanding of PFA, (2) applying PFA principles (look, listen, link), (3) effective communication techniques with victims, and (4) handling violence from both legal and psychological perspectives. The implementation methods include knowledge transfer sessions, interactive discussions, field practice, and the provision of supporting booklets. This approach is designed to enhance the cadres’ skills in providing practical and human-centered support to victims. Based on qualitative evaluations, the program has improved the knowledge of PPPA cadres in Pemalang Regency regarding: (1) basic understanding of psychological first aid, (2) prioritizing and adopting a victim-centered perspective, and (3) strengthening victim assistance in both legal processes and psychological support needs. The service team has also developed a related module to enable cadres to continue improving their skills independently.